Efektivitas Media Pembelajaran Berbasis Augmented Reality Untuk Meningkatkan Keterampilan Berpikir Kritis pada Materi IPAS - Ongke Ageng Pamorti; Winarno; Kartika Chrysti Suryandari (Jurnal Penelitian Pendidikan IPA, 2024)
Technology in the 5.0 revolution is developing very rapidly so it is necessary to prepare the student to face the challenges of the 21st century by having 21st century skills, namely critical thinking Having a low category of critical thinking because the teacher in using the media has not facilitated students to think critically tends to be monotonous and boring. The purpose of this experiment is to establish the effective of AR media to improving learners' critical thinking skills on IPAS material. The study used quantitative research methods with the research type true experiment with pretest-posttest control group design. The data collection methods used are test instrument. The results of the study were tested Independent T-Test to find out the enhancing students' critical thinking skills then conducted an effectiveness test to determine the effectiveness of the application of Augmented Reality-based learning media to improve critical thinking skills on IPAS material. The research results of the average value of the experimental class using AR media are 58.92 and 75.98 while the average value of the control class using conventional media is 58.80 and 63.56. The test results of the Independent Sample T-Test obtained with a value of 0.000 with the provisions of the test decision if significant less than 0.05 then there is sig. effects among the experimental and control posttests. The effective test using N-Gain obtained a result of 56.52 which was categorized as sufficient. It is synthesized that AR-based learning media improves critical thinking skills and the effectiveness of AR-based learning media is effective to use with the N-Gain test.